The prevalence of metabolic syndrome in patients with non-alcoholic fatty liver disease in Erbil city - Maryam Abdulwahid; Altun Mahmood; Hussein Yousif (Advanced Medical Journal)
Background and objectives: Non-alcoholic fatty liver disease is the accumulation of fatty units in the liver in the absence of other triggers. Its development may have been primarily caused by metabolic syndrome, so the purpose of this study is to identify the prevalence of metabolic syndrome in non-alcoholic fatty liver disease and then to discover which parameter has the strongest link with non-alcoholic fatty liver disease.